Unlocking the techno-economic potential of biomass gasification for power generation Comparative analysis across diverse plant capacities - Kamaruzaman, Nursyuhada' (Waste management (New York, N.Y.), 2024)
Copyright © 2024 Elsevier Ltd. All rights reserved.